Deep Venous Reflux Associated with a Dilated Popliteal Fossa Vein Reversed with Endovenous Laser Ablation and Sclerotherapy. (23rd October 2013) - Link, Daniel P.; Feneis, Jennifer; Carson, John
Abstract : Objective . To report an incidence of reflux in the deep venous system reversed by ablation of a popliteal fossa vein (PFV). Method . A 40-year-old man with pain and swelling in the medial upper calf was found to have an incompetent PFV. Results . Reflux in the femoral and popliteal veins was reversed utilizing endovenous laser ablation and foam sclerotherapy, documented on Duplex studies before and after the intervention. There was also resolution of symptoms. Conclusion . A PFV can be associated with deep venous reflux. Correction of this reflux with ablation of the PFV suggests that his type of reflux is secondary to volume effects of the incompetent popliteal vein.